THE APPLICATION OF THE CAUSE COMPANY'S NEEDS AGAINST THE COVID-19 PANDEMIC: A CRITICAL ANALYSIS (Revista Paradigma, 2020)
The coronavirus disease transformed into a pandemic that hit the entire world, affecting various areas of modern life and the economy, and put State services to the test, especially social security, which includes social pensions, social assistance and public health. In our labor doctrine, many companies found themselves at an impasse, looking for alternatives to face social isolation measures, which had impacts on the market, and together with emergency public policies, understand how they could handle labor conflicts. In Chilean labor law, there is a cause for dismissal due to company needs - Article 161 of the Specific Code - which will probably be widely applied in future times. However, it is necessary to understand if this cause could effectively be used to end employment contracts in the face of the COVID-19 pandemic. The present article tries to argue on this topic and propose practical solutions that, according to Labor Law, can guide the use of the causal needs of the company and legal consequences.